A phenomics approach to the analysis of the influence of glutathione on leaf area and abiotic stress tolerance in Arabidopsis thaliana - Schnaubelt, Daniel; Schulz, Philipp; Hannah, Matthew A.; Yocgo, Rosita E.; Foyer, Christine H. (Frontiers in Plant Science, 2013)
Reduced glutathione (GSH) is an abundant low molecular weight plant thiol. It fulfils multiple functions in plant biology, many of which remain poorly characterised. A phenomics approach was therefore used to investigate the effects of glutathione homeostasis on growth and stress tolerance in Arabidopsis thaliana. Rosette leaf area was compared in mutants that are either defective in GSH synthesis (cad2, pad2 and rax1) or the export of γ-glutamyl cysteine and GSH from the chloroplast (clt) and in wild type plants under standard growth conditions and following exposure to a range of abiotic stress treatments, including oxidative stress, water stress and high salt. In the absence of stress, the GSH synthesis mutants had a significantly lower leaf area than the wild type. Conversely, the clt mutant has a greater leaf area and a significantly reduced lateral root density than the wild type. These findings demonstrate that cellular glutathione homeostasis exerts an influence on root architecture and on rosette area. An impaired capacity to synthesise GSH or a specific depletion of the cytosolic GSH pool did not adversely affect leaf area in plants exposed to short term abiotic stress. However, the negative effects of long term exposure to oxidative stress and high salt on leaf area were less marked in the GSH synthesis mutants than the wild type. These findings demonstrate the importance of cellular glutathione homeostasis in the regulation of plant growth under optimal and stress conditions.